Philosophy, A Challenge To Post-Truth, Also in Indonesia - Franz Magnis-Suseno (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
This article insists that it is the task of philosophy to challenge untruth under the guise of truth. In the first part the author follows how philosophy changed from teachings of wisdom to critique of false truth claims: beginning with Eastern philosophy, with special consideration of Javanese wisdom, through Greek philosophy where philosophy comes into its own right, to Medieval philosophy, until enlightenment clearly establishes philosophy as criticism. Hegel and Critical Philosophy are given special attention. In the second part the author stresses the importance of critical philosophy for Indonesia. He exemplifies this on three widely accepted untruths: untruth about what happened in Indonesia in 1965 and 1966, the claim that Pancasila is incompatible with liberal democracy, and the claim of religious extremism to present truth about religion. The article ends with appeal to defend our democratic freedoms without compromise.